Increased low frequency fluctuation in the brain after acupuncture treatment in CSVDCI patients: A randomized control trial study - Yang, Nan; Chen, Sina; Liu, Shuxue; Ling, Shuiqiao; Chen, Lidian (Frontiers in Neuroscience, 2023)
Background: Cerebral small vessel disease (CSVD) is one of two cognition-impairing diseases. Acupuncture (Acu) is a flexible treatment with few adverse effects and is thus widely used to treat neurological problems. Methods: We recruited a total of 60 patients and assigned them to two groups (n=30 each group). During the study, some participants were excluded by quality control, and a total of 44 subjects (25 Acu and 19 controls) were completed to investigate the therapeutic efficacy of acupuncture on CSVD cognitive impairment (CSVDCI). The following demographic and clinical variables were compared between the two groups: gender, age, education, smoking, alcohol, Montreal cognitive assessment (MoCA), symbol digit modalities test (SDMT), verbal fluency test (VFT), digit span task (DST), Boston naming test (BNT) scores, and amplitude of low-frequency fluctuation (ALFF) under the typical band (0.01-0.08Hz). Mixed effect analysis was utilized to test for differences between the two groups before and after the treatment. Results: Following acupuncture treatment, the Acu group scored higher on MoCA, SDMT, VFT, DST, and BNT compared to controls (P < 0.05). The brain regions showing substantially greater ALFF values in the Acu group were the right inferior temporal gyrus, left middle occipital gyrus, left superior occipital gyrus, left insula, bilateral postcentral gyrus, right superior parietal gyrus, right cerebellum, right precuneus, and right precentral gyrus (P < 0.005, no correction). The ALFF values in the right inferior temporal gyrus (P = 0.027), left middle occipital gyrus (P = 0.005), left superior occipital gyrus (P = 0.011), and right superior parietal gyrus (P = 0.043) were positively associated with MoCA. Conclusion: We found that acupuncture modulates the functional activity of temporal, occipital, and parietal regions of the brain in CSVDCI patients.